High-Performance Indirect Current Control Scheme for Railway Traction Four-Quadrant Converters - He, Liqun; Xiong, Jian; Ouyang, Hui; Zhang, Pengju; Zhang, Kai (IEEE transactions on industrial electronics (1982), 2014)
In the recent development of railway traction drives, four-quadrant converters are widely adopted at the grid side as front-end converters. Since the switching frequency of such megawatt-rated converters is limited to several hundreds of hertz, the bandwidth of the current controller is usually restricted. In addition to feedback control of instantaneous current, indirect current control (ICC) is also an alternative in high-power low-switching-frequency applications. Suffering from the inherent cross coupling between active and reactive power as well as sluggish response of ac current, traditional ICC is not a perfect solution for power conversion. To realize the independent control of active and reactive power, a phasor diagram arranged in an orthogonal coordinate system is introduced. In order to improve the dynamic performance of ICC, a transient-free current control method is proposed after analyzing the characteristic of ac current response in detail. In addition, a large-signal model of dc voltage loop, which is based on the conception of average power control, is set up. Finally, robustness to circuit parameters and adaptability to weak grids are certified for the transient-free controller. Both simulation and experimental results are presented to prove the validity of the proposed control scheme.